Women Chewing Gum: Feminist Critical Analysis of Advertising as Symbolic Violence - NAS, ALPARSLAN (ANKARA UNIV, FAC COMMUNICATION, 2015)
Representation of women in advertisements has been a crucial point of debate in critical studies on advertising and gender. Advertising has critically been evaluated as an ideological apparatus that reproduces gender roles and promotes sexism. In addition to overt forms of sexist representations, advertisements also construct implicit meanings of gender inequality, which is difficult to recognize. The aim of this article is to show that advertisements generate symbolic violence that normalizes and legitimizes gendered relations of power so that gender inequalities would be misrecognized. Based on Pierre Bourdieu's notion of symbolic violence, this article analyzes the image of women chewing gum in an advertisement campaign by Falim, Turkey's leading chewing gum brand with feminist critical analysis. Falim advertisements portray women who are pressured by patriarchy but do not resist it and are content with it. Eventually, the patriarchal narrative brings forth the normalization of gender inequalities and its communication to the wider public via advertising as a rhetorical device.
Keywords: Advertising; symbolic violence; feminism; gender; male hegemony